Improvement Efforts in Construction Equipment Management at Central Services Division PT. Freeport Indonesia - Dewantoro, Bartholomeus; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2012)
The main goal of every construction project is to finish the project on the approved budget, on time and to achieve the required quality. Central Services Division’s of PT. Freeport Indonesia (PTFI) primary responsibility is to manage all capital construction projects approved by Freeport each year. In the past five years (2006 - 2011), Freeport had spent U.S. $600 million investment per year in the form of AFE (Approved for Expenditure) of which 20% - 40% of the fund was managed by Central Services Division to build new facilities. The 2008 records showed that 58% of the projects had been delayed in project completion. Further analysis showed that failure in providing necessary equipment support was the third basic cause in project completion. Equipment Control Section in Central Services Division has the responsibility to manage all construction equipment required by the division in completing projects that have been assigned.The focus of this final project is on improving the effectiveness of Equipment Control Section organization in managing construction equipment. The challenge ahead is that the construction of new facilities of DMLZ and GBC underground mine which is expected to begin its production in 2016.The method used to increase the effectiveness of the organization is the McKinsey 7S Framework. The methodology was conducted by reviewing organization effectiveness of Equipment Control Section based on the 7S elements: Skills, Shared Values, Style, Staff, System, Structure and Strategy at the current condition. By determining the future, expected condition of the organization, then, a gap analysis between the two conditions is conducted. The next step is to determine business strategies in each of the 7S elements with the major goal of eliminating or minimizing that gap.Implementation plan to eliminate gap depends on commitment of Equipment Control Section management. Without increase in effectiveness in managing construction equipment, completion of all construction projects that meet the principles of cost, quality and schedule will be impossible to achieve. Keywords: McKinsey 7S Framework, effectiveness, equipment, gap analysis, current condition, expected condition